Cell Surface CD74-MIF Interactions Drive Melanoma Survival in Response to Interferon-γ - Tanese, Keiji (J Invest Dermatol, 2015)
While melanoma is believed to be a highly immunogenic tumor and recent developments in immunotherapies are promising. Interferon-γ (IFN-γ) produced by immune cells plays a crucial role in tumor immune surveillance; however, it has also been reported to be pro-tumorigenic. In the current study, we found that IFN-γ enhances the expression of CD74, which interacts with its ligand, macrophage migration inhibitory factor (MIF), and thereby activates the PI3K/AKT pathway in melanoma, promoting tumor survival. IFN-γ increased phosphorylation of AKT Ser473 and upregulated total and cell surface expression of CD74 in human melanoma cell lines tested. CD74 was highly expressed in melanoma tissues. Moreover, the expression of CD74 on tumor cells correlated with plasma IFN-γ levels in melanoma patient samples. In our analysis of melanoma cell lines, all produced MIF constitutively. Blockade of CD74-MIF interaction reduced AKT phosphorylation and expression of pro-tumorigenic molecules, including interleukin-6, interleukin-8 and BCL-2. Inhibition of CD74-MIF interaction significantly suppressed tumor growth in the presence of IFN-γ in our xenograft mouse model. Thus, we conclude that IFN-γ promotes melanoma cell survival by regulating CD74-MIF signaling, suggesting that targeting the CD74-MIF interaction under IFN-γ–stimulatory conditions would be an effective therapeutic approach for melanoma.